2005
DOI: 10.1111/j.1469-8137.2005.01346.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among growth, development and plastic response to environment quality in a perennial plant

Abstract: Summary• Phenotypic traits differ between plants in different environments and within individuals as they grow and develop. Comparing plants in different environments at a common age can obscure the developmental basis for differences in phenotype means in different environments. Here, we compared trait means and patterns of trait ontogeny for perennial ( Viola septemloba ) plants growing in environments that differed in quality either naturally or due to experimental manipulation.• Consistent with predictions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 44 publications
4
58
1
1
Order By: Relevance
“…In this species, water potentials decreased sharply after exposure to drought, which correlated with high mortality rates. Consistent with predictions for adaptive stress resistance, perennial plants allocate proportionately more biomass to roots and rhizomes and produce smaller, thicker, and longer-lived leaves than those plants grown near optimal conditions (Moriuchi and Winn, 2005). Increased resource allocation to roots, particularly in rhizomes, is a stress resistance trait, because as discussed before, roots (and particularly, tubers and rhizomes as perennial storage organs) provide the safety to resume growth when environmental constraints, such as water or nutrient availability, have passed.…”
Section: Stress Resistancesupporting
confidence: 63%
“…In this species, water potentials decreased sharply after exposure to drought, which correlated with high mortality rates. Consistent with predictions for adaptive stress resistance, perennial plants allocate proportionately more biomass to roots and rhizomes and produce smaller, thicker, and longer-lived leaves than those plants grown near optimal conditions (Moriuchi and Winn, 2005). Increased resource allocation to roots, particularly in rhizomes, is a stress resistance trait, because as discussed before, roots (and particularly, tubers and rhizomes as perennial storage organs) provide the safety to resume growth when environmental constraints, such as water or nutrient availability, have passed.…”
Section: Stress Resistancesupporting
confidence: 63%
“…For some of annual plant species, nutrient availability affects the root shoot biomass partitioning, only when it changes early in ontogeny (McConnaughay and Coleman, 1998). However, it is also reported that plants can alter their initial trajectory in response to even later increase in nutrient resources (Moriuchi and Winn, 2005). In the present study, at low nutrient availability in coarse sediments, the biomass allocation to roots is obviously higher (St.1 and St.2), while at a higher nutrient availability in finer sediments, more fraction of biomass is allocated to aboveground tissues (St.3 and St.5).…”
Section: Plasticity In Biomass Allocation To Aboveground and Belowgromentioning
confidence: 41%
“…Similarly, a smaller leaf area may be an effective adaptive mechanism to the terrestrial habitat, possibly because a smaller leaf area can result in decreasing water loss by transpiration (Oikawa et al, 2006). Therefore, the production of smaller, longer-lived leaves in lower-quality environments may be a more adaptive approach to increase resource use efficiency in response to stress (Chapin et al, 1993;Kikuzawa, 1991;Moriuchi and Winn, 2005). The present study also suggests that terrestrially grown plants have thinner lamina than aquatically grown plants.…”
Section: Discussionmentioning
confidence: 57%